Land degradation risks associated with cemetery leachate: Generation, transport, and management strategies - de Castro, Jeffrey H.; Lunag Jr., Marcelino N. (Journal of Degraded and Mining Lands Management, 2026)
Cemeteries are long-established cultural landscapes that remain largely overlooked as potential sources of environmental contamination and land degradation. Burial processes generate leachates enriched with organic matter, nutrients, heavy metals, and pathogenic organisms, which can migrate through soils and pose risks to groundwater, nearby surface waters, and associated ecological systems. This review synthesizes current knowledge on leachate generation, composition, and transport mechanisms, and evaluates existing pollution mitigation and land management practices applicable to cemetery landscapes. A database-driven literature assessment reveals notable research gaps, including limited multidisciplinary approaches, insufficient attention to emerging contaminants, and scarce studies addressing impacts beyond soil and water, such as air quality, vegetation dynamics, ecological succession, and biodiversity. Although engineering, vegetative, and regulatory strategies have been proposed, their implementation and effectiveness vary widely across regions and often remain at the conceptual stage. The review highlights the need for integrated assessment and management frameworks to support environmentally sustainable and socially sensitive cemetery planning.